A Bibliometric Analysis of Chickpea Agronomic Practices in the World During 45 Years of Scientific Research - Claudio Calia; Cataldo Pulvento; Mohamed Houssemeddine Sellami; Luigi Tedone; Claudia Ruta; Giuseppe De Mastro (Legume Science, 2024)
ABSTRACT Chickpea (Cicer arietinum L.) cultivation practices underwent significant transformation in recent decades due to advancements in scientific knowledge and the need for sustainable, productive farming systems. In this study, a bibliometric analysis of scientific publications from 1977 to 2023 on chickpea agronomic practices was conducted, revealing critical insights. India, as the world's leading chickpea producer, plays a pivotal role, not only in production but also as a significant contributor to scholarly research and international collaborations. The choice of journals for publication is found to influence research impact. Analysis of research trends using co‐occurrence networks of keywords reveals evolving focuses, with a recent shift towards qualitative aspects, such as protein content and nutritional quality, as well as sustainable agricultural practices. The study also emphasizes the necessity for further research on chickpea quality characteristics, strategies to mitigate antinutritional factors, yield optimization, and the impact of climate change on chickpea cultivation. Ultimately, chickpea cultivation research holds great promise in contributing to global food security and environmental sustainability. This bibliometric analysis provides a comprehensive overview of chickpea cultivation research and offers valuable insights for researchers, policymakers, and stakeholders as they navigate the future of sustainable agriculture and the quest for protein‐rich food production while minimizing the environmental footprint.